Alien life : the search for extraterrestrials and beyond / Barry Parker ; drawings by Lori Scoffield. - Parker, Barry R. (Plenum Trade, 1998)
"Pointing up to the heavens, today's cutting-edge radio telescopes scan the cosmos for any signal that may indicate alien life, as tantalizing prospects lead us further along our quest. Already we may have found microbes in meteorites from Mars. As Parker points out, three of Jupiter's moons are now known to contain ice and liquid water - leading some scientists to believe that perhaps under this ice lie hidden areas teeming with aquatic life. After discovering planets outside our solar system, astronomers believe that other "suns" may exist capable of supporting planets that harbor alien life-forms. Beyond making contact, Parker stresses that disaster surely awaits us on Earth as its ever-growing population depletes our planet's natural resources. He delineates the plans to mine treasures in space, generate power on distant bodies, and establish thriving communities in space."--BOOK JACKET. "We can control our alien searches in space, but what if they find us first? Have we already been visited? Have humanoid creatures with large black eyes actually hovered over our towns? How do we account for eyewitness reports of bizarre glowing lights, "scorched" patterns on crop fields, and alleged abductions? Parker investigates the truth surrounding these visits and discusses the UFO phenomenon."--Jacket.